Knowledge, attitude, and practice of doctors and nurses about the disposal of expired and unused medicines in Dhaka city - Fardin Al Fahad Shakib, Tainur Ratul, Mohammad Borhan Uddin (Journal of Applied Pharmaceutical Science, 2025)
Improper medicine disposal practice has become a major concern in South Asian countries. Many healthcare professionals are not aware of safe medicine disposal practices. This survey study aimed to assess the knowledge, attitude, and practice (KAP) of unused and expired medicines among doctors and nurses in Dhaka City. A questionnaire-based, cross-sectional survey was conducted among 150 respondents. Respondents were classified into two categories: doctors = 100, and nurses = 50. Data collection was done using a pre-validated, structured questionnaire. Collected data were added to the MS Excel spreadsheet and analyzed by Statistical Package for Social Science version 23.0. Two-thirds of the nurses kept expired medicines in their houses as they did not want to waste them whereas 50% of doctors had expired medicines. Remarkably, 42.86% of nurses responded to immune system deficiencies resulting from improper medicine disposal, while it figured 28.16% among doctors. Alarmingly, 95.46% of nurses disposed of medicines via flush in the toilet/basin or dump in the dustbin, and 69.79% of doctors followed similar practices. 27.43% of doctors and 13.85% of nurses recommended reducing the number of medicines from prescription. It has been suggested that health policymakers work together with healthcare professionals and general people by launching public awareness campaigns.
Keywords: Unused medicines, expired medicines, disposal practices, doctors, nurses, Dhaka city, pharmaceutical waste management